Factors for shaping the organizational views and leadership practices of Ibrahim Rugova - Nikci Rexha, Elmire (Technium Social Sciences Journal, 2022)
Analyzing the unique figure of the scholar, writer, politician and diplomat, as well as the key views of the former President of Kosovo Dr. Ibrahim Rugova expressed during the leadership of the political process of state-building in Kosovo. Through this paper I aimed to present the role of political communication as well as leadership in the defining leadership of the masses. Studying the leadership, charisma and political and public communication of Dr. Rugova, we encounter an essential difference in political and public communication between President Rugova and prominent world leaders throughout history. A great deal of space is occupied by the communication of his political and programmatic vision through political doctrine and active peaceful resistance. From the multidimensional treatment of the Rugova leadership elaborated through political-public communication, unique leadership and pragmatism in leading the unfolding of his program vision, he managed to convince the local and international public to be sensitized with his mission. The strategy of political leadership, treated through the prism of public and political communication, highlights a unique doctrine for the realization of the right to self-determination, and the creation of political and state identity. This political doctrine can be defined as "fighting the negative will of the enemy", which is a long-term intellectual war that requires intellectual patience, restrained and coordinated action, and constructive knowledge.